Ongoing pregnancy in a woman who inadvertently underwent office hysteroscopy during early pregnancy - (:unkn) unknown (ELSEVIER SCIENCE INC, 2005)
Objective: To report a case of ongoing pregnancy in a woman who underwent hysteroscopy during the implantation phase. Design: Case report. Setting: A university hospital. Patient(s): A 34-year-old woman with unexplained infertility who was scheduled for IVF. Intervention(s): Office hysteroscopy. Main Outcome Measure(s): Hysteroscopy during early pregnancy. Result(s): An ongoing pregnancy after hysteroscopy during the implantation phase. Conclusion(s): The risk of a properly performed hysteroscopy in the implantation phase of an unrecognized pregnancy may be less than expected. (C)2005 by American Society for Reproductive Medicine.
Keywords: pregnancy; hysteroscopy; implantation phase; INVITRO FERTILIZATION; CYCLES